Comportamiento productivo de pollos de carne línea COBB-VANTRESS 500 en diferentes estaciones del año 2009 - Mendoza León, Jorge David (2011)
This research aims to evaluate the performance of broilers Cobb-V antress 500 raised under the open shed system in different seasons of the year 2009. 1200 were used for chickens (3 00 birds per season, 150 males and 150 females per group ), the farm is located in the district of Huanchaco, Trujillo province, department of La Libertad, at an altitude of 50msnm. The treatments were: T1 (Summer), T2 (auturnn), T3 (winter) and T4 (spring). We evaluated the weight gain, feed intake, feed conversion, mortality, productive efficiency index and index-Ortiz Ingalls. Each treatment was given 4 different diets, which had levels isoenergetic and isonitrogenous. After four consecutive seasons m which each treatment comprised a season it was concluded that the best weight gain was found in T4 (spring) 2751.62g, followed by T2 (winter) by the treatments 2702.53gy T2 and TI with 2700.47gy 2562.68g respectively, similarly, the best feed conversion was shown by T4 to 1.95 Statistically, the best treatment was T4 (p <0.05), showing no differences in the T3 and T2, although these treatments were statistically different from T1. The best food consumption at present the treatment T4 and T3 which the temperature does not exceed the thermal neutral zone of bird. The best index of productive efficiency was shown by T4 with 348.43 points and the best index Ingalls-Ortiz was shown by T3 (1.43).